2021
DOI: 10.1039/d1cy00920f
|View full text |Cite
|
Sign up to set email alerts
|

Co2(CO)8 and unsaturated epoxides as unexpected partners in generating functionalized siloxane oils and cross-linked materials

Abstract: Herein, we describe the unexpected ring opening of the epoxide group of allyl glycidyl ether and 4-vinylcyclohexene oxide in polymethylhydrosiloxane (PMHS) hydrosilylation reaction using 0.1 mol% of Co2(CO)8 as catalyst....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…25 This complex could also perform the crosslinking of industrially relevant allyl glycidyl ether or 4-vinylcyclohexene oxide as unconventional tethers with PMHS. 26 This catalytic system thus offered a unique method for the cross-linking of PMHS with traditional dienes and unconventional organic tethers, such as (un)saturated esters. These results showed that catalytic systems based on commercially available and structurally simple non-noble metal complexes (without specific ligands) could be of interest in the field of hydrosilylation.…”
Section: Introductionmentioning
confidence: 99%
“…25 This complex could also perform the crosslinking of industrially relevant allyl glycidyl ether or 4-vinylcyclohexene oxide as unconventional tethers with PMHS. 26 This catalytic system thus offered a unique method for the cross-linking of PMHS with traditional dienes and unconventional organic tethers, such as (un)saturated esters. These results showed that catalytic systems based on commercially available and structurally simple non-noble metal complexes (without specific ligands) could be of interest in the field of hydrosilylation.…”
Section: Introductionmentioning
confidence: 99%